Analysis of some of the success factors and product strategies Applied Research in the industrial sector of the Iraqi - الكعبي, نعمة شليبة; مصطفى, رشا فالح (Journal of Economics and Administrative Sciences, 2015)
This research deals with the study of the relationship between the success factors as the independent variable and product strategies as the dependent variable , has reacted to these variables to form the frame , which is the research which centered research problem about the extent to which industrial companies the vision and knowledge of Muslim women survive and develop in the business market , which can be expressed about the extent of awareness of corporate success factors and the use of product strategies and what the relationship between the factors and strategies , while expressing the importance of research to make the focus on the product occupies a paramount importance in the industrial sector companies in relation to the elements of the marketing mix for the possibility of face -based competition , as embodied objectives of the research in the diagnosis and the reality of organizations surveyed about the extent of its ability to provide chances of success necessary for product strategies , and test relationships influence success factors and product strategies in companies that have been researched and to identify the degree of variation of the success factors in product strategies in corporate research sample . Was chosen as the three sectors under the Ministry of Industry and Minerals and took a sample of managers and formed a questionnaire and there were 108 questionnaires distributed for this purpose and was the most prominent results are the existence of a correlation between the success factors and strategies as well as a correlation effect nonsmoker companies were homogeneous